2014
DOI: 10.1002/j.0022-0337.2014.78.12.tb05845.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Preferences and Performance in Crown Design: Conventional Wax‐Added Versus CAD

Abstract: The purpose of this study was to evaluate dental students' perceptions of traditional waxing vs. computer-aided crown design and to determine the effectiveness of either technique through comparative grading of the inal products. On one of two identical tooth preparations, second-year students at one dental school fabricated a wax pattern for a full contour crown; on the second tooth preparation, the same students designed and fabricated an all-ceramic crown using computer-aided design (CAD) and computer-aided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…For comparison, Tran et al ( 23 ) reported that dentists from the United Kingdom had undertaken only training of CAD/CAM technology by companies providing CAD/CAM systems, private courses or were taught by other CAD/CAM users, while participants did not mention CAD/CAM education at the School. Due to the fact that dental students have a higher preference for visual learning than general student population ( 24 ), Illinois and Indiana University Schools of Dental Medicine incorporated CAD/CAM in their curriculum, in order to enable students to virtually design crowns using CAD techniques ( 13 , 14 ). The authors ( 13 , 14 , 25 ) reported that incorporating of CAD/CAM technology in preclinical and clinical curriculum positively affects students’ attitudes regarding CAD/CAM technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, Tran et al ( 23 ) reported that dentists from the United Kingdom had undertaken only training of CAD/CAM technology by companies providing CAD/CAM systems, private courses or were taught by other CAD/CAM users, while participants did not mention CAD/CAM education at the School. Due to the fact that dental students have a higher preference for visual learning than general student population ( 24 ), Illinois and Indiana University Schools of Dental Medicine incorporated CAD/CAM in their curriculum, in order to enable students to virtually design crowns using CAD techniques ( 13 , 14 ). The authors ( 13 , 14 , 25 ) reported that incorporating of CAD/CAM technology in preclinical and clinical curriculum positively affects students’ attitudes regarding CAD/CAM technology.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that dental students have a higher preference for visual learning than general student population ( 24 ), Illinois and Indiana University Schools of Dental Medicine incorporated CAD/CAM in their curriculum, in order to enable students to virtually design crowns using CAD techniques ( 13 , 14 ). The authors ( 13 , 14 , 25 ) reported that incorporating of CAD/CAM technology in preclinical and clinical curriculum positively affects students’ attitudes regarding CAD/CAM technology. In this study, most of PS and CS students consider CAD/CAM technology useful, and many of them highlighted the shorter fabrication time as the main reason.…”
Section: Discussionmentioning
confidence: 99%
“…Khot et al () conjectured that 3D learning is facilitated via a series of 2D images but increases the cognitive load and effort, especially for the participants with poorer spatial ability (Khot et al, ). The spatial ability of dental students is a predictor of success especially in the preclinical courses (Hegarty et al, ) with student viewing dynamic 3D animations to improve their mental models (Douglas et al, ). Furthermore, spatial ability has been linked to improved understanding in anatomy (Qi et al, ) and oral radiology (Nilsson et al, ) in cohorts of dental students.…”
Section: Introductionmentioning
confidence: 99%
“…Cement dissolution can cause loss of retention with loosening of the restoration, ceramic chipping, and marginal discolorations. All these elements are translated into functional or aesthetic failure of dental crowns [8][9][10][11][12][13][14]. Previous studies propose various limits as acceptable for marginal discrepancies, Mclean recommended 120 µm while von Fraunhoder recommended 100 µm.…”
Section: Introductionmentioning
confidence: 99%